2014
DOI: 10.1177/1087057114541149
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Hippocampal Neural Stem/Progenitor Cells and Their Application to Physiologically Relevant Assays for Multiple Ionotropic Glutamate Receptors

Abstract: The hippocampus is an important brain region that is involved in neurological disorders such as Alzheimer disease, schizophrenia, and epilepsy. Ionotropic glutamate receptors-namely,N-methyl-D-aspartate (NMDA) receptors (NMDARs), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptors (AMPARs), and kainic acid (KA) receptors (KARs)-are well known to be involved in these diseases by mediating long-term potentiation, excitotoxicity, or both. To predict the therapeutic efficacy and neuronal toxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Western blot analysis showed that labels a band of 47-50 kD, and it was characterized by using immunohistochemistry in mouse (Stevens et al, 2010). Our staining with this antibody matched that from original descriptions of Pax6 immunostaining in the developing cortex (Gotz et al, 1998), our previous publications (Martinez-Cerdeno et al, 2012; Cunningham et al, 2013a), and more recent work from unrelated laboratories (Fukushima et al, 2014; Maury et al, 2015). The database link for PAX6 in Homo sapiens (human) .…”
Section: Methodssupporting
confidence: 83%
“…Western blot analysis showed that labels a band of 47-50 kD, and it was characterized by using immunohistochemistry in mouse (Stevens et al, 2010). Our staining with this antibody matched that from original descriptions of Pax6 immunostaining in the developing cortex (Gotz et al, 1998), our previous publications (Martinez-Cerdeno et al, 2012; Cunningham et al, 2013a), and more recent work from unrelated laboratories (Fukushima et al, 2014; Maury et al, 2015). The database link for PAX6 in Homo sapiens (human) .…”
Section: Methodssupporting
confidence: 83%
“…Here, we identified proliferative effects and first hints towards the underlying molecular mechanism of the rapid-acting and long-lasting antidepressant ketamine in human NPCs. The undifferentiated human iPSC-derived NPCs used in our study displayed typical characteristics of hippocampal NPCs by upregulating neuronal progenitor markers such Nestin and Pax6 while missing expression of functional ionotropic glutamate receptors, such as NMDA or AMPA receptors, which is in accordance with the previously described characterization of hippocampal human undifferentiated NPCs [9,28,39].…”
Section: Discussionsupporting
confidence: 89%
“…Cells were seeded at a density of 3.0 × 10 5 cells per ml and incubated for 24 h. The following day, the medium was removed and cells were loaded with 4 µM Fluo-8 (AAT Bioquest) as the indicator dye, reconstituted in a modified Tyrode’s assay buffer (10 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES), 135 mM NaCl, 5 mM KCl, 2.5 mM CaCl 2 , and 10 mM glucose adjusted to pH = 7.4.) and incubated for 30 min at 37 °C and 5% CO 2 , and another 30 min at room temperature in the dark [27,28]. Then, the Fluo-8 loading buffer was removed and replaced with fresh Tyrode’s assay buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Before neural differentiation, expanded HIP-009 cells were harvested and cultured in Neural Transition Medium (PhoenixSongs Biologicals) added with transition medium supplement cocktail (Neural Transition Supplement, 10 ng/mL bFGF, 20 ng/mL EGF, and 1 µg/mL laminin) and 30 µg/mL gentamicin for 3 days. 14 The expansion and transition treatment of HIP-009 cells was carried out at 37 °C in a humidified atmosphere of 2% O 2 , balanced with N 2 and 6% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%